SEVERAL PROPERTIES OF CONVERGENT AND CAUCHY SEQUENCES IN A QUASI 2-NORMED SPACE - Malčeski, Risto (Matematichki Bilten, 2015)
In [7] C. Park has generalized the term quasi-normed space, i.e. has given the term quasi 2-normed space. Further, C. Park has proven few properties of quasi 2-norm, in [3] M. Kir and M. Acikgoz have given the procedure for completing the quasi 2-normed space and in [1], [4] and [6] are proven few inequalities about quasi 2-normed spaces. In this paper are proven several properties of Cauchy and convergent sequences in a quasi 2-normed space. Some of them are analogy to the properties of such sequences in n-normed spaces ([5], [8]).